2013
DOI: 10.1159/000350021
|View full text |Cite
|
Sign up to set email alerts
|

Intraparenchymal Cyst Development after Deep Brain Stimulator Placement

Abstract: Following deep brain stimulation (DBS) surgery, a variety of potential mechanical or functional complications ranging from perioperative events to hardware malfunction may occur. We present 2 patients who developed a unique complication of cyst formation at the tip of the DBS electrode in the absence of infection. One patient had a unilateral ventral intermediate lead placement for essential tremor, and the other had bilateral subthalamic nucleus (STN) placement for Parkinson's disease. After a period of sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…In subsequent reports, Ramirez-Zamora et al , in 2012, and Baxi et al , in 2014, also described intraparenchymal cyst development in patients after DBS placement. The former report included two patients who developed neurological deficits over a time period of 3–6 months, where the cyst formation was limited to the tip of the DBS electrode 9. The latter report described two patients who were incidentally found to have asymptomatic non-infectious cysts, also mostly located at the tip of the electrode lead 8.…”
Section: Discussionmentioning
confidence: 99%
“…In subsequent reports, Ramirez-Zamora et al , in 2012, and Baxi et al , in 2014, also described intraparenchymal cyst development in patients after DBS placement. The former report included two patients who developed neurological deficits over a time period of 3–6 months, where the cyst formation was limited to the tip of the DBS electrode 9. The latter report described two patients who were incidentally found to have asymptomatic non-infectious cysts, also mostly located at the tip of the electrode lead 8.…”
Section: Discussionmentioning
confidence: 99%
“…Both cysts resolved after removal of the DBS lead. These investigators suggested that the cause of cyst formation was tracked CSF during placement of the DBS lead or, alternatively, because of an autoimmune or inflammatory response to the DBS hardware …”
Section: Discussionmentioning
confidence: 99%
“…These investigators suggested that the cause of cyst formation was tracked CSF during placement of the DBS lead or, alternatively, because of an autoimmune or inflammatory response to the DBS hardware. 4,5 Acute brain parenchymal reaction resulting from lead insertion has been suggested as a mechanism for rare findings of low-attenuation signal around the DBS lead after surgery by Kim et al 6 They described 7 cases of transient increased lowattenuation signals that circumferentially surrounded DBS electrodes. The signal extended into the subcortical white matter and was associated with unexpected and transient neurological symptoms during the immediate postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…Ramirez‐Zamora recently presented two cases of intraparenchymal cysts after DBS surgery. This is also a rare complication that can be clinically difficult to differentiate from delayed intracerebral electrode infection . The best radiological follow up for diagnosis of abscess or edema along the electrodes is MRI, which can be safely carried out with the stimulator off in a 1.5 T camera.…”
Section: Discussionmentioning
confidence: 99%